Endovascular Treatment of Acute Ischemic Stroke Due to Isolated Proximal Posterior Artery Occlusion - Zhang, Guang; Zhu, Yujing; Ling, Yeping; Chen, Pingbo; Dai, Jiaxing; Wang, Chunlei; Xu, Shancai; Shumadalova, Alina; Shi, Huaizhang (Frontiers in Surgery, 2022)
Background: Acute ischemic stroke (AIS) due to isolated proximal posterior cerebral artery (PPCA) occlusion is rare but associated with high morbidity and mortality rates. However, the optimal treatment strategy for patients with AIS caused by PPCA remains unclear. We discuss our single-center experience with endovascular treatment (EVT) in patients with PPCA. Methods: Data from patients with AIS due to PPCA occlusion were retrospectively analyzed. We analyzed procedural details, the degree of reperfusion, functional outcomes, and complications. Functional outcomes were determined using the modified Rankin Scale (mRS) at 90 days, and good outcome was defined as mRS 0–2 at 90 days. Successful reperfusion (modified treatment for cerebral ischemia 2b−3) after endovascular therapy. Safety variables included symptomatic hemorrhage (defined as an increase of four or more points in the National Institute of Health Stroke Scale score), vessel perforation or dissection, and new ischemic stroke in different territories. Results: Seven patients were included in this study. The mean age of the patients was 64 ± 12.4 years. Successful reperfusion was achieved in all seven patients (100%). Good outcomes were achieved at 90 days in 2 patients (28.6%), and favorable outcomes were observed in five patients (71.4%). One patient underwent angioplasty as rescue therapy after three attempts. One patient died because of severe gastrointestinal bleeding 24 h after EVT, which was probably a complication of intravenous alteplase. One patient had an embolism in the basilar artery and achieved complete reperfusion after rescue thrombectomy. Another patient had a complication of vessel dissection in the PPCA and underwent stent implantation as rescue therapy. We observed no recurrence of ischemic stroke or any intracranial hemorrhage on non-contrast computed tomography 24 h after the procedure. Conclusion: EVT may represent an alternative treatment strategy for patients with acute ischemic stroke caused by PPCA.